Terapi Herbal Jinten Hitam dalam Peningkatan Haemoglobin pada Ibu Menyusui dengan Anemia - Ranny Septiani; Nurchairina Nurchairina; Nora Isa Trinovadela; Herlina Herlina (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2021)
Background: One of the world's health problems in developing countries is anemia. Nationally, anemia is common in women. Anemia is very dangerous for both mother and baby. Anemia in breastfeeding mothers will affect the quality of breast milk so that it affects the nutritional fulfillment of their babies. Purpose: To determine the effectiveness of giving black cumin to breastfeeding mothers with anemia in Bandar Lampung City in 2020. Methods: This study is a quasi-experimental study with pre and post-test designs. The treatment in this study was giving black cumin. While the variables to be studied are hemoglobin levels in the blood of breastfeeding mothers before and after the intervention. The sample in this study was breastfeeding mothers who suffered from anemia in Bandar Lampung City. Bivariate data analysis used the T-test to determine the difference in hemoglobin levels before and before offering black cumin. Results: This study showed that the administration of black cumin had an average hemoglobin level before administration of black cumin the average hemoglobin level after administration of black cumin (p=0,001), resulting in an increase in the average hemoglobin level of 1.84 dl/gr. Conclusion: The use of black cumin as an effective complementary therapy (complementary) in the treatment of anemia in lactating mothers with anemia.Abtrstark. Latar Belakang : Salah satu masalah kesehatan di dunia pada negara berkembang adalah anemia. Secara nasional anemia banyak terjadi pada perempuan.Anemia sangat berbahaya bagi ibu dan bayinya. Anemia pada ibu menyusui akan mempengaruhi kualitas ASI sehingga mempengaruhi pemenuhan nutrisi bayinya.Tujuan : mengetahui efektifitas pemberian jinten hitam pada ibu menyusui dengan anemia di Kota Bandar Lampung tahun 2020. Metode: Penelitian ini merupakan penelitian quasi eksperimendengan desain pre dan post test. Perlakuan dalam penelitian ini adalah pemberian jinten hitam. Sedangkan variabel yang akan diteliti adalah kadar hemoglobin dalam darah ibu menyusui sebelum dan setelah diintervensi. Sampel pada penelitian adalah ibu meyusui yang menderita anemia di Kota Bandar Lampung. Analisis data bivariat menggunakan uji T untuk mengetahui beda kadar haemoglobin sebelum dan sesudah pemberian jinten hitam. Hasil : Penelitian ini didapat hasil pemberian jinten hitam mempunyai nilai rata-rata kadar hemoglobin sebelum pemberian jinten hitam rata-rata kadar hemoglobin setelah pemberian jinten hitam (p=0,001). Sehingga, terjadi peningkatan rata-rata kadar hemoglobin sebesar 1,84 dl/gr.. Simpulan: Penggunakan jinten hitam efektif sebagai terapi komplementer (pelengkap) dalam pengobatan anemia pada ibu menyusui dengan anemia.